VARIASI POLA SIMETRI ROTASI 90 DERAJAT DARI SIMULASI SISTEM DINAMIK DENGAN TIGA TES KONVERGENSI - Kintan Febri Cania; Mahdhivan Syafwan; Arrival Rince Putri (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This article reviews the  symmetry pattern which has  rotational symmetry and translational symmetry along the -axis and -axis. The  symmetry pattern is generated through the implementation of Matlab application using discrete dynamical system simulation, after analysing the requirements and determining the appropriate dynamical function. In this context, each point on the plane serves as the starting point in the iteration of the dynamical system. The colour assigned to each point is determined by the number of iterations performed. The generation of the  symmetry pattern involves three convergence tests, namely the Euclidean Test, the Fractional Distance Test, and the Maximum Distance with Weighted test. Through a variety of dynamic function parameter combinations, a more visually appealing and diverse range of  symmetry patterns is obtained.